Fracture plane based failure criteria for fibre-reinforced composites under three-dimensional stress state. (15th November 2018) - Li, N.; Gu, J.F.; Chen, P.H.
Abstract: Fracture plane based failure criteria for fibre-reinforced composite materials under three-dimensional stress state are presented. The failure function is taken as a polynomial expansion in terms of the stress components on fracture plane, which provides a general mathematical technique for constructing Mohr's fracture hypothesis-based criteria. The polynomial expansion is then truncated at the quadratic terms to approximately describe the failure function. Besides the basic strengths of UD laminates, the fracture plane angles under transverse tension/compression and pure shear are introduced to calibrate the failure criteria, since Mohr's concept can be described completely and exactly only by both the basic strengths and the fracture plane angles. According to experimental evidences, the interaction between matrix-dominated and fibre-dominated failure modes is also considered in the present study. No empirical or artificially defined parameters are included in the criteria. Experimental verification for different kinds of unidirectional composites under various stress states demonstrates that the proposed failure criteria have a good predictive ability.